REFORMASI MESIR: BERKACA PADA INDONESIA? - Herdi Sahrasad (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2016)
Nowadays, Egypt is in the hand of military that leads Egypt to the democratic life. In the same time, it was reported by media masses that one of five Egyptians lived under poverty line, and the 12% inflation reduced Egyptians income dramatically and caused impediment to get education, basic need and health. After Mubarak, Egyptian reformation is far from over. Will Egypt reformation be in common with Indonesia? How should Egypt be governed post-Mubarak? How are political, economic and social circumstances of Egypt after Mubarak? This paper explores deeply those questions.